Dexter. The fifth season [videorecording (DVD)] - Hall, Michael C., 1971-; Carpenter, Jennifer, 1979-; Vélez, Luna, 1964-; Lithgow, John, 1945-; Zayas, David; Lindsay, Jeffry P. (CBS DVD, 2011)
In season five, Dexter goes from happily married husband to guilt-ridden single dad. How will it affect his ability to maintain an average-guy facade while satisfying his need to kill?